2008
DOI: 10.1002/ca.20645
|View full text |Cite
|
Sign up to set email alerts
|

The three‐dimensional arrangement of the myocytes in the ventricular walls

Abstract: The arrangement of the myocytes aggregated together within the ventricular walls has been the subject of anatomic investigation for more than four centuries. The dangers of analyzing the myocardium on the basis of arrangement of the skeletal myocytes have long been appreciated, yet some still described the ventricular myocardium in terms of a unique band extending from the pulmonary trunk to the aorta. Another current interpretation, with much support, is that the ventricular myocytes are compartmentalized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 46 publications
1
75
0
Order By: Relevance
“…It is this distribution of ␣ t that was used in the FIB simulation. Meanwhile, more recent experimental investigations have confirmed the earlier observations by Streeter and colleagues that myofiber orientation in the LV wall has a component in transmural direction (1,13,18,23,24,25,32). Accurate quantification of ␣ t has proven to be difficult, among others, because the unique definition of a wall-bound coordinate system to which the fiber orientation can be referred to is difficult (13).…”
Section: Discussionmentioning
confidence: 78%
“…It is this distribution of ␣ t that was used in the FIB simulation. Meanwhile, more recent experimental investigations have confirmed the earlier observations by Streeter and colleagues that myofiber orientation in the LV wall has a component in transmural direction (1,13,18,23,24,25,32). Accurate quantification of ␣ t has proven to be difficult, among others, because the unique definition of a wall-bound coordinate system to which the fiber orientation can be referred to is difficult (13).…”
Section: Discussionmentioning
confidence: 78%
“…Thompson et al (Thompson et al, 2010a) showed in D. pealeii that the inner surface of the mantle experiences 1.3 to 1.6 times greater circumferential strain than the outer surface at any time point during the exhalant phase of a jet. Because circular fibers are oriented in transverse planes of the mantle and also appear to follow a perfectly circumferential trajectory, there are no architectural specializations, such as those found in mammalian cardiac ventricle muscle (Lunkenheimer et al, 2004;Anderson et al, 2006;Anderson et al, 2009) or vertebrate skeletal muscles (Alexander, 1969;Rome and Sosnicki, 1991;Wakeling and Johnston, 1999;Azizi et al, 2008) that could permit all of the fibers to experience approximately the same range of strains during jetting. Thus, the transmural gradient of circumferential strain in the mantle may require muscle fibers from the inner surface to operate farther left on the ascending limb of the length-tension curve at any instant during mantle contraction.…”
Section: Mantle Kinematics and In Vivo Muscle Operating Length Rangementioning
confidence: 99%
“…2 Ideally, engineered tissues should have the same characteristics as the tissues that they were designed to mimic. For many tissues such as the myocardium, 3 smooth muscle, 4 and skeletal muscle, 5 the tissue function is closely linked to the cell organization and alignment. Therefore, controlling the structure and properties of the tissues by changing the extracellular matrix composition and substrate topography is crucial for proper cell alignment, organization, and differentiation.…”
Section: Introductionmentioning
confidence: 99%